2013
DOI: 10.1007/s11356-013-1633-x
|View full text |Cite
|
Sign up to set email alerts
|

PFAS profiles in three North Sea top predators: metabolic differences among species?

Abstract: Profiles of seven compounds of perfluoro-alkyl substances (PFASs) were compared among three species of top predators from the Danish North Sea: the white-beaked dolphin (Lagenorhynchus albirostris), the harbor porpoise (Phocoena phocoena), and the harbor seal (Phoca vitulina). The seals had higher total burdens (757.8 ng g(-1) ww) than the dolphins (439.9 ng g(-1) ww) and the porpoises (355.8 ng g(-1) ww), probably a reflection of feeding closer to the shore and thus contamination sources. The most striking di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 58 publications
3
54
1
Order By: Relevance
“…As expected, the sensitivity for all compounds dramatically decreased (around 20 times) for the M +• transitions when adding water as modifier, while at the same time the intensity for [M+H] + transitions improved around 1.5 times. This occurred for all the compounds except for Br [6][7][8][9][10] BDEs and DBDPE for which a 2-fold decrease was observed for [M+H] + . When adding HCOOH 1%, the sensitivity of [M+H] + transitions remained almost the same as with only water.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As expected, the sensitivity for all compounds dramatically decreased (around 20 times) for the M +• transitions when adding water as modifier, while at the same time the intensity for [M+H] + transitions improved around 1.5 times. This occurred for all the compounds except for Br [6][7][8][9][10] BDEs and DBDPE for which a 2-fold decrease was observed for [M+H] + . When adding HCOOH 1%, the sensitivity of [M+H] + transitions remained almost the same as with only water.…”
Section: Resultsmentioning
confidence: 88%
“…As a result of bans, the use of novel BFRs, such as decabromodiphenyl ethane (DBDPE) and 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE), used in replacement of Deca-BDE and Octa-BDE mixtures, respectively, and the use of organophosphorus flame retardants is increasing [1][2][3] . Several reviews have reported the analytical methods commonly used for the determination of PBDEs in environmental and biological matrices [4][5][6][7][8][9][10] . Gas chromatography (GC) coupled to mass spectrometry (MS) operating in both electron ionization (EI) and electron capture negative ionization (ECNI) modes using quadrupole (Q), triple quadrupole (QqQ) or ion trap (IT) analyzers are the techniques most widely used 2,[11][12][13][14][15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of their use for more than 60 years, residues of PFAS are widely spread in the environment [2,3]. Some of these compounds can bioaccumulate and biomagnify in the food chain [4][5][6], and have been detected in humans [7,8]. The ubiquitous presence of these PFAS in the general population, their long half-lives, and increasing evidence of potential adverse health effects, is of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Galatius et al (2013) measured the contaminant profiles of a range of PFASs in three marine mammal species (white-beaked dolphin, harbour porpoise and harbour seals) from the North Sea and observed some interesting species differences in bioaccumulation behaviour. Nordén et al (2013) studied the transfer of PFAAs from eggs to developing chicks in two wild bird species (great cormorant and herring gull).…”
mentioning
confidence: 99%